2020
DOI: 10.9734/arrb/2020/v35i230194
|View full text |Cite
|
Sign up to set email alerts
|

Hematoprotective and Gastroprotective Effects of Cnidoscolus aconitifolius (Linn)-Supplemented Diet in Male Wistar Rats

Abstract: Aims: Cnidoscolus aconitifolius (CA) is a plant known to possess very high phenolic compound. The study evaluated hematological indices, anti-oxidative properties and gastroprotective potentials of CA leaf-supplemented diet. Methodology: Male Wistar rats weighing between 80-100 g were divided into 5 groups of n=18. Group 1 animals were fed with normal diet and groups 2-5 were fed with diets supplemented with 1%, 2.5%, 5% and 10% of C. aconitifolius powdered leaves continuously for 4, 8 and 12 weeks. Hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…It has been reported that chaya leaf meal (CLM) can be used as a feed ingredient up to 20% in blue shrimp [ 14 ]. An increase in BW gain (BWG) was found in the rats fed 5%, and 10% of CLM-supplemented diets [ 10 ]. The use of 15%–25% CLM inclusion in commercial diets showed similar BWG and FI compared with the chickens fed in the CLM-free group, but feed efficiency decreased in the CLM groups [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that chaya leaf meal (CLM) can be used as a feed ingredient up to 20% in blue shrimp [ 14 ]. An increase in BW gain (BWG) was found in the rats fed 5%, and 10% of CLM-supplemented diets [ 10 ]. The use of 15%–25% CLM inclusion in commercial diets showed similar BWG and FI compared with the chickens fed in the CLM-free group, but feed efficiency decreased in the CLM groups [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, heterophils, eosinophils, and monocytes were linearly increased in the birds fed DCLM inclusion diets compared with the control. Chaya leaves can modify the blood parameters in Wistar rats [ 10 ], and chaya leaf extract was shown to improve blood components in Wistar rats with induced diabetes [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracts of P. tuberregium sclerotia and C. aconitifolius leaves have been reported to protect the liver and kidney (Oyagbemi and Odetola, 2010 ; Saba et al, 2010 ; Adaramoye and Aluko, 2011 ; Adaramoye et al, 2011 ; Ikewuchi et al, 2017 ; Iwu et al, 2020 ). They have also been reported to be hypolipidaemic, anti-diabetic (Oladeinde et al, 2007 ; Ikewuchi et al, 2013a , 2021d ; Achi et al, 2017 ; Ifeanacho et al, 2019a ), anti-hypertensive (Ikewuchi et al, 2013a , 2014 ), and haematomodulatory (Azeez et al, 2010 ; Ifeanacho et al, 2020 ; Iwu et al, 2020 ; Onasanwo et al, 2020 ). In the present study, the ability of aqueous extracts of P. tuberregium sclerotia and C. aconitifolius leaves to regulate plasma markers of kidney and liver function/integrity was investigated in doxorubicin-treated rats.…”
Section: Introductionmentioning
confidence: 99%